Evaluation of Stock Listing Impact on Corporate Performance of Agro-Food Companies in Vietnam. - Linh Bao, Dinh Thi (2019)
This thesis investigates the effect of the stock market listing on corporate performance of agricultural and food processing (agro-food) companies listed in the Vietnamese stock market. Most important data is extracted from published annual report of agro-food companies listed on the stock exchange of Vietnam. We also use data and information from a survey carried out by the Ministry of Agriculture and Rural development of Vietnam on activities of 200 agricultural companies in 10 provinces of the country and data from annual surveys by the Vietnam General Office of Statistics. While the descriptive statistics serve to compare corporate performance before and after the stock market listing, regression models are used to determine the relationships between independent variables and dependent variables. A total factor productivity (TFP) model is modified for the case of Vietnam in order to examine the impact of the stock market listing on the value added, which is a proxy of corporate performance of these companies. The results show that in general, being listed in the stock market has positive effect on corporate performance, but the effect on ROC and EPS is clearer than on other performance proxies. The review and analysis of policies affecting agro-food corporate performance in Vietnam is also carried out for analyzing impact factors and for providing recommendations. Main findings lead to different groups of recommendations for Vietnamese Government and companies in this sector. In general, the Vietnamese Government should push up the equitization of SOEs in the agro-food sector and encourage them to improve corporate performance by different ways, of which, being listed in the stock market is an important one.